Evaluation The Development Of Diversity Students Elementary School - Dadan Nugraha; Firgina Amelia Nur Husni; Ateng Ruhendi; Andewi Suhartini (Comunitario: Jurnal Pengabdian Masyarakat, 2025)
This research aims to find out the evaluation of the student diversity development program at SDIT Al-furqon. This type of research is descriptive research. The approach used in this study is a qualitative approach. The result of this research is an evaluation of students' religious development covering three aspects, namely: 1. Cognitive aspect: tahfiz qur'an program, memorizing prayers, writing verses evaluation which is carried out orally and written tests, 2. Affective aspect, in this aspect SDIT focuses on forming a disciplined, honest and polite attitude. The instruments used in this evaluation are direct observation/observation by the teacher, 3. Psychomotor/skills aspects, through getting used to the practice of obligatory prayers and congregational prayers, Islamic holiday commemoration activities which contain many Islamic activities and competitions, lightning boarding schools. Evaluation of this program is usually seen from the activity journal provided by the school.